A Comparison between Total Intravenous Anaesthesia using Propofol plus Remifentanil and Volatile Induction/Maintenance of Anaesthesia using Sevoflurane in Children Undergoing Flexible Fibreoptic Bronchoscopy. Issue 6 (November 2013) - Chen, L.; Yu, L.; Fan, Y.; Manyande, A.
Flexible fibreoptic bronchoscopy is an important tool in the evaluation and management of paediatric respiratory disease. Total intravenous anaesthesia (TIVA) and volatile agent induction and maintenance of anaesthesia (VIMA) are commonly used for these procedures. The aim of this study was to determine which is superior for children undergoing flexible fibreoptic bronchoscopy. The study included two phases. In Phase 1, ED99 of propofol in TIVA and ED99 of sevoflurane in VIMA were first determined. In Phase 2, 50 children aged from one to three years were recruited and randomly assigned to either a TIVA or a VIMA group. An ED99 dose of propofol with remifentanil was administered to the TIVA group and sevoflurane to the VIMA group. Haemodynamic variables, stress hormone responses, anaesthesia profiles, adverse reactions and physicians' levels of satisfaction were compared between the two groups. The ED99 values of propofol in the TIVA group and sevoflurane in the VIMA group were 8.9 μg/ml and 6.8% respectively. Haemodynamic variables and stress hormone levels were higher in the VIMA group than in the TIVA group. Agitation and coughing also occurred less frequently in the TIVA group. In addition, physicians' levels of satisfaction were greater in the TIVA group. Our results suggest that TIVA with propofol plus remifentanil is superior to VIMA using sevoflurane alone for children undergoing flexible fibreoptic bronchoscopy.